2019
DOI: 10.1111/nep.13527
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating haemodialysis patient's nutritional status: Body mass index or body cell mass index?

Abstract: Objective Evaluate which of two combinations of parameters based on International Society of Renal Nutrition and Metabolism recommendations could better identify patients with protein‐energy wasting (PEW) and to compare the relationship of these two combinations with other clinical and body composition parameters. Methods This was a multicentre longitudinal study with 24 months of follow‐up. The PEW patients were characterized by: Group A (GA) – normalized protein catabolic rate (nPCR) < 1.0 g/kg per day, albu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Body cell mass, which corresponds to fat-free mass without bone mineral mass and extracellular water, is the metabolically active compartment of the body. 15 We found that poor body cell mass index was independently associated with hypomagnesemia. 10,15 Another advantage of the body cell mass index is that this compartment excludes extracellular water, avoiding possible masking of the nutritional status.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Body cell mass, which corresponds to fat-free mass without bone mineral mass and extracellular water, is the metabolically active compartment of the body. 15 We found that poor body cell mass index was independently associated with hypomagnesemia. 10,15 Another advantage of the body cell mass index is that this compartment excludes extracellular water, avoiding possible masking of the nutritional status.…”
Section: Discussionmentioning
confidence: 70%
“…18 In peritoneal dialysis patients, low serum Mg levels are associated with poorer nutritional status, deteriorating cellular health, increased inflammation, and lower BMI. 10,15 Another advantage of the body cell mass index is that this compartment excludes extracellular water, avoiding possible masking of the nutritional status. Body cell mass, which corresponds to fat-free mass without bone mineral mass and extracellular water, is the metabolically active compartment of the body.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations